Fuel Consumption Comparison of Different Battery/Ultracapacitor Hybridization Topologies for Fuel-Cell Vehicles on a Test Bench - Vural, Bulent; Dusmez, Serkan; Uzunoglu, Mehmet; Ugur, Enes; Akin, Bilal (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2014)
The power train of fuel-cell vehicles (FCVs) can be composed of onboard hybrid energy sources to reduce fuel consumption, extend driving range through regenerative braking energy recovery, and possibly increase the specific power density. One of the main issues significantly affecting the FCV performance is the chosen hybrid system topology along with system components, which requires research to find the best hybrid structure for the lowest fuel consumption. Although several hybridization topologies have been studied separately in the literature, an overall investigation and fuel consumption comparison of the most promising fuel-cell (FC) power-train topologies along with the experimental verification should be realized. In this regard, this paper demonstrates a detailed comparison of four different hybrid FC power-train configurations with feasible battery and ultracapacitor (UC) combinations, on a test bench using normalized ECE-15 drive cycle. The results demonstrate that the lowest equivalent fuel consumption can be achieved with FC/battery/UC hybrid combination.
Keywords: Fuel economy; fuel-cell vehicles (FCVs); hybridization topologies; power electronics; regenerative braking energy; DC-DC CONVERTER; HYBRID ELECTRIC VEHICLES; ENERGY-STORAGE SYSTEMS; POWER-SYSTEM; BATTERY; ULTRACAPACITOR; MANAGEMENT; SUPERCAPACITOR; DESIGN; ONLINE; Engineering